Easily-prepared bimetallic metal phosphides as high-performance electrode materials for asymmetric supercapacitor and hydrogen evolution reaction. (18th October 2019) - Gou, Jianxia; Du, Yunmei; Xie, Shengli; Liu, Yanru; Kong, Xiangjin
Abstract: Transition metal phosphides are very attractive because of the remarkable performance in energy storage and conversion. Herein, a series of bimetallic phosphides are synthesized through a one-step solid-state reaction. The obtained bimetallic phosphides show outstanding properties as supercapacitor electrode materials. Results show that the incorporation of secondary metal into phosphides tunes composition, electronic structure and then the electrochemical performance. And electrochemical properties are closely associated with the secondary metal content. Notably, the obtained NiCoP shows the best performance with 2011 F g −1 at 1 A g −1 . And an asymmetric supercapacitor (ASC) based on NiCoP shows energy density of 47.6 W h kg −1, along with 90.5% of capacitance maintained after 10000 cycles. In addition, the NiCoP also possesses great performance toward hydrogen evolution reaction (HER), which displays the lowest potential of 0.221 V vs. RHE and 0.173 V vs. RHE at 10 mA cm −2 in 0.5 M H2 SO4 as well as 1.0 M KOH, respectively. The excellent properties may result from the enhanced electrical conductivity, synergistic effects among metal elements and the increased local electrical dipole. The regulation of electronic structure through introduction of secondary metal atom sheds considerable light on realization and preparation of the bimetallic transition metal compounds as electrode materials. Highlights: Electronic structure is related to the secondary metal content. NiCoP shows outstanding performance with 2011 and 1461 F g −1 at 1 and 10 A g −1 . Excellent property is due to increased local electrical dipole and conductivity. NiCoP holds promise as outstanding electrode material in asymmetric supercapacitor. NiCoP shows excellent electrocatalytic performance toward HER in both acidic and alkaline solutions.